Prison and forensic mental health staff after suicides in their care. A narrative review of international and German national evidence - Fontao, María Isabel; Bulla, Jan; Ross, Thomas (Frontiers in Psychiatry, 2024)
There is a growing body of international research investigating the impact of patient suicide on mental health professionals. The experience of losing a patient to suicide can have a significant and, in some cases, long-lasting (negative) impact on mental health professionals. However, the nature and extent of the impact on prison staff or forensic mental health professionals in particular is less clear. This narrative review summarises both quantitative and qualitative studies and key findings in this area, focusing on the above professions. A literature search was conducted using PsychInfo and Google Scholar, covering the period from 2000 onwards. The vast majority of findings relate to mental health professionals in general. We were unable to identify any published reports on the responses of forensic psychiatric staff. The majority of identified studies in the prison context are qualitative. Studies from German-speaking countries are particularly scarce in both the prison and mental health contexts. We conclude that there is a profound lack of knowledge about the impact of client/patient suicide on the subgroups of (German) prison and forensic psychiatric staff. Clearly, more research is needed on both the nature and extent of the impact, as well as on the specific organisational and supportive factors that help to mitigate the negative effects of suicide.